Effect of microstructure and low cycle fatigue deformation on tensile properties of P91 steel. Issue 8 (18th August 2020) - Mariappan, K.; Shankar, V.; Bhaduri, A.K.
Abstract: Isothermal furnace heat treatments were carried out to simulate the microstructures of inter‐critical, fine grain and coarse grain heat‐affected zones of P91 steel weld joint at different soaking temperatures ranging from just above AC1 (837 °C) to well above AC3 (903 °C). Interrupted low cycle fatigue tests were performed on the specimens of P91 steel up to 5 %, 10 %, 30 %, and 50 % of the total fatigue life at the strain amplitude of ±0.6 %, strain rate of 0.003 s −1 and temperatures of 550 °C and 600 °C. Subsequently, tensile tests were conducted on the interrupt tested specimens at the same strain rate and temperatures. Soaking at the inter‐critical temperature region reduces / deteriorates the tensile and yield strengths of base metal compared to fine grain and coarse grain regions. The inter‐critical heat‐affected zone accounted higher damage contribution towards the overall tensile behavior of the actual P91 steel weld joint. Substructural coarsening during strain cycling at elevated temperatures attributes to the rapid reduction in the initial yield strength up to 10 % of fatigue life of P91 steel. A higher amount of plastic strain accumulation during low cycle fatigue deformation resulted in a decrease in fatigue life of the inter‐critical heat‐affected zone of P91 steel. Abstract : The influence of prior cyclic deformation on the tensile properties of the simulated microstructures of P91 heat‐affected zone is examined. Drastic reduction in the yield strengths of all the microstructures within the initial 10 % of fatigue life is attributed to substructural coarsening during cyclic deformation.